COMMUNICATION SKILLS OF INDONESIAN EMPLOYEESIN LOCAL, NATIONAL, AND MULTINATIONAL COMPANIES: CULTURAL AND SYMBOLIC CAPITAL - Setyorini, Nanis (Dinamika : Jurnal Sastra dan Budaya, 2018)
AbstractThis qualitativeresearch aimed to understand the objective and subjective perspectives of Indonesian employees on their communication skills in local, national, and multinational companies. Therefore, semi-structured interviews were applied to managers and junior satff to collect data. Furthermore, Bourdieu's framework of capital was used for data analysis. The results showed that all participants collectivelly agreed that communication skills were essential abilities for meeting their occupational requirements, instead of technical skills. They particularly relate their communication skills with their English language proficiencydue to global business markets. Subjectivelly, the managers argued that communication skills were important to support their daily office duties, mobilising professional opportunities, and to elevate job placements. While, the junioremployees constructed their communication skills in relation to English certificates, job application, and to increase social status. In brief, this research indicated the complex understandings of cultural and symbolic communication skills in the three workplace contexts.Keywords: communication skills, employees, companies, imaginary and needs